The Value of Spirituality in Keluarga Persilatan Ki Ageng Pandan Alas - Muhammad Hanif (Budapest International Research and Critics University, 2021)
Pencak silat is cultured in Madiun and pencak silat has become an icon of the Madiun Regency government as